Evaluation of a real-time PCR assay performance to detect Mycobacterium tuberculosis, rifampicin, and isoniazid resistance in sputum specimens: a multicenter study in two major cities of Indonesia - Parwati, Ida; Chaidir, Lidya; Yunus, Muhammad; Montain, Maya Marinda; Budhiarko, Dini; Selasih, Siti Fatimah; Ristandi, Ryan Bayusantika; Rachman, Rifky Waluyajati; Nurhayati, Raden Desy; Pambudi, Imran; Budiyati, Akterono Dwi (Frontiers in Microbiology, 2024)
Background Tuberculosis (TB) is one of the major global health issues due to its high mortality rate, especially in low- and middle-income countries. One of the key success points of the TB eradication program is early TB diagnosis, which requires rapid and accurate diagnostic testing. This study aimed to evaluate the performance of a newly developed RT-PCR kit (Indigen MTB/DR-TB RT-PCR) in a routine TB clinical setting. Method A multi-fluorescence RT-PCR assay was designed and developed to detect regions within IS6110, rpoB, katG, and inhA of the Mycobacterium tuberculosis (MTB) genes. Sputum specimens were obtained from suspected TB patients who visited TB healthcare facilities in two major cities of Indonesia from September 2022 to May 2023. Specimens were assessed using Indigen MTB/DR-TB RT-PCR, acid-fast bacillus (AFB) smear microscopy, MTB culture, and drug susceptibility testing (DST) methods. Fisher’s exact test (χ2) was used to analyze the Indigen performance relative to culture methods. Result The performance of Indigen MTB/DR-TB RT-PCR to detect MTB was assessed using 610 sputum specimens obtained from suspected patients. The overall sensitivity and specificity were 94.12% (95% CI: 90.86–96.48%) and 98.32% (95% CI: 96.20–99.46%), respectively. When the analysis was performed on AFB smear-negative TB subjects (386 subjects), a lower sensitivity level was found at 78.57% (95% CI: 68.26–86.78%), while the specificity level remained similar at 98.34% (95% CI: 96.18–99.46%). The overall performance of Indigen MTB/DR-TB RT-PCR to detect MTB showed substantial agreement with the MTB culture method (kappa value 0.93). In comparison to DST, the sensitivity and specificity levels of Indigen to detect RIF resistance or INH resistance were 78.2% (95% CI: 61.8–90.2%) and 82.8% (95% CI: 64.2–94.2%), respectively, while the specificity level for both groups was at 100% (95% CI, 87.7–100%). Conclusion Indigen MTB/DR-TB RT-PCR demonstrated reliable performance for TB molecular diagnostic testing and can be implemented in routine TB diagnostic settings.